The Synthesis of the System SiO2-Gd2O3-Eu2O3 and Research on the Acid-Base Properties and Kinetics of Particle Formation in This System - Sabukhi I. Niftaliev; Irina V. Kuznetsova; Nhat Anh Tran (Materials Proceedings)
This study investigates the synthesis and characterization of SiO2-Gd2O3-Eu2O3 nanomaterials. The sol–gel method was employed using tetraethoxysilane (TEOS), gadolinium nitrate, and europium nitrate as precursors. The influence of rare earth oxide concentration on the hydrolysis kinetics and activation energy was evaluated. Additionally, the acid-base properties of the synthesized materials were examined using the Hammett indicator adsorption method. The results revealed that the addition of Gd2O3 and Eu2O3 oxides to the system accelerated the hydrolysis process and reduced the activation energy. The formation of a layered structure, consisting of a central Si(OH)4 nucleus, a Si-O-Si polymer layer, and hydrated metal ion layers, was observed. The acid-base properties of the synthesized nanomaterials were influenced by the drying method and the composition of the system. The findings provide valuable insights into the synthesis and properties of SiO2-Gd2O3-Eu2O3 nanomaterials, which have potential applications in various fields such as optoelectronics and catalysis.